Characteristics study of ammonia-n and phosphorus in sewage wastewater effluent: a case study of Alkhumrah, Jeddah Wastewater Treatment Plant. Issue 1 (August 2021) - Saleh, A A S; Ibrahim, N; Awang, N R; Akbar, N A
Abstract: Ammonia-N (NH3 -N) and Phosphorus (P) pollutions remain highly challenging pollutants to the Saudi environment. The sewerage treatment plant can be one of the main contributors to NH3 -N and P pollutants. The main aim of this study is to investigate the concentration of NH3 -N and P released from the Al Khumrah wastewater treatment plant in Jeddah. The treatment process used in this treatment plant consists of screening, aerated grit removal chambers, surface aeration, sedimentation and sludge thickening and de-watering via belt filter presses. For this study, primary data of N and P is obtained from the Ministry of Environment & Agriculture, Kingdom of Saudi Arabia. The data is collected from the wastewater treatment plant of Al Khumrah, Jeddah. A total of 101 data is collected for NH3 -N and P within a period of 6 months from September 2019 to February 2020. Descriptive statistic was used to analyse the data. It was found that the highest mean concentration of NH3 -N and P in the effluent are 4.2 mg/L and 1.7 mg/L respectively. The concentration of NH3 -N and PO4 3- in the influent exceeded the maximum limit of 1.0 mg/L stated in General Environmental Regulations and Rules for Implementation (2001) provided by the Kingdom of Saudi Arabia Presidency of Meteorology and Environment. A low effluent concentration is set up by the authorities to meet the requirement of water reuse and recycling. The result has shown that the removal efficiency of NH3 -N during the treatment is 55%. However, the removal efficiency of PO4 3- is very inconsistent with the percentage removal varied from 0%-61.5 %. This finding demonstrated that the treatment plant will continuously not be able to comply with the standard discharge limit especially if a higher concentration of NH3 -N and PO4 3- entering the treatment plant. In this case, the changes of the current treatment process or addition of tertiary treatment would be needed to ensure the discharge wastewater met the reuse and recycling requirement.